Patent Legal Protection On Invention (Comparation Study Between Indonesia and Japan) - Salsabila Khairunnisa (Jurnal Hukum Novelty, 2018)
The development of technology is needed and cannot be separated from patent protection between WIPO’s (World Intellectual Property Organization) member like Indonesia and Japan. This study discusses Indonesian patent protection law and its comparison toward invention between Indonesia and Japan. The study done through normative research methodology and analysed it comparatively. Indonesia has regulated the patent protection in Act Number 13 of 2016. The scopes are patent, simple patent, and also the period of patent protection for 20 years, while regular patent protected for only 10 years. Japan has arranged the patent protection in Japan Patent Act 21/1959 and it covers the patent and utility model. The time period for the patent protection is 20 years and for utility models is 6 years. The two countries have used common principle that is ‘first to file’. Both nations have also required the same requirements which are the novelty of the invention, the beneficial of the product, and the invention steps. Litigation and non-litigation are the doors to resolve patent dispute.